THE THERMODYNAMIC AND LATTICE VIBRATIONAL PROPERTIES OF CuPd ALLOY UNDER HYDROSTATIC PRESSURE - Kazanç, Sefa (My University, 2019)
In this paper, the effects of hydrostatic pressure on the thermodynamic and vibrational properties such as bulk modulus, secondorder elastic constants, acoustic phonon frequencies, density of state (DOS) and Grüneisen parameters (?) on Cu-%20Pd alloyswas examined by using the molecular dynamics (MD) simulation. Interaction forces between atoms in the model system werecalculated by Quantum Sutton-Chen (Q-SC) potential energy function. The simulation results obtained from this study werecompared with the experimental and theoretical results in the literature.
Keywords: Termodinamik; Fizikokimya